O-3 Bereavement help points: an innovative and collaborative approach to providing bereavement support. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Archer, Nikki; Leech, Ian; Chetwynd, Helen
Abstract : For 25 years St Giles Hospice has provided bereavement support for families and friends of patients it cares for. The development of community based Bereavement Help Points (BHP), delivered in partnership with other local organisations and services enabled us to address a number of issues which we faced, with minimal investment. As a service we were facing: increased demandfrom within the local community to widen access to bereavement support recognition that our services were not broad enough to meet the needs of all bereaved people a need to be able to increase responsiveness and access to support, both in terms of response times and geographical location a challenge to develop services with no additional funding A scoping exercise was undertaken to identify existing service providers and gaps in service provision. Following this initial consultation we launched a pilot BHP in collaboration with a local NHS Acute Trust, the service was delivered by trained volunteers. It provided open access to a weekly drop in, support group and access to information. The initial pilot gave us an evidence base, shaping the development of additional weekly BHPs delivered by volunteers throughout our catchment area, working in partnership with a variety of organisations. These include CRUSE South Staffs, The Dove Service, Queens's Hospital Burton, Hospice Hope, CRUSE Burton, Ian Hazel Funerals, and Tesco's. We are currently undertaking data analysis to understand who, when, how the BHPs are being used. Early analysis indicates: 34% have had contact with the hospice 66% not 38% attend for one contact, others on an ad hoc basis, some weekly high user satisfaction levels Development of the BHPs has generatednew and exciting relationships, it hasenhanced our offer of bereavement support services, widened access, and enabled a community engagement and partnership approach to providing bereavement support with minimal investment.